2003
DOI: 10.1021/ja0362196
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Rectification and Conductance Switching in Carbon-Based Molecular Junctions by Structural Rearrangement Accompanying Electron Injection

Abstract: Molecular junctions were fabricated consisting of a 3.7 nm thick layer of nitroazobenzene (NAB) molecules between a pyrolyzed photoresist substrate (PPF) and a titanium top contact which was protected from oxidation by a layer of gold. Raman spectroscopy, XPS, and AFM revealed that the NAB layer was 2-3 molecules thick and was bonded to the two conducting contacts by C-C and N-Ti covalent bonds. The current/voltage behavior of the PPF/NAB(3.7)/Ti junctions showed strong and reproducible rectification, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
194
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(202 citation statements)
references
References 69 publications
7
194
1
Order By: Relevance
“…We recognize that such a plot tends to convert a range of data into linear relationships but point out that the greatest deviation (ref 6 by McCreery et al in Figure 5) differs in calculated and observed values by only a factor of 8. The fact that the azo compound ( Figure S5 in the SI) described by McCreery et al 6 does not follow the expected trend ( Figure 5) for the "spherical" approximation but does for the "extended" approximation is easily rationalized: this group could be trans-extended, and therefore ordered, at the surface of the SAM. Correspondingly, the compound reported by Ashwell et al 10 is composed of the bulky terminal group and the thin alkyl backbone ( Figure S5 in the SI) and plausibly disordered.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 87%
“…We recognize that such a plot tends to convert a range of data into linear relationships but point out that the greatest deviation (ref 6 by McCreery et al in Figure 5) differs in calculated and observed values by only a factor of 8. The fact that the azo compound ( Figure S5 in the SI) described by McCreery et al 6 does not follow the expected trend ( Figure 5) for the "spherical" approximation but does for the "extended" approximation is easily rationalized: this group could be trans-extended, and therefore ordered, at the surface of the SAM. Correspondingly, the compound reported by Ashwell et al 10 is composed of the bulky terminal group and the thin alkyl backbone ( Figure S5 in the SI) and plausibly disordered.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 87%
“…Graphitic carbons have many attractive characteristics, including ease-ofhandling, low-cost, high mechanical stability and good electrical conductivity. The material is readily available in a number of forms including high surface area felts and cloths suitable as supports for combinatorial chemistry [1,2], carbon powders useful for chromatography [3], glassy carbon (GC) [4], a convenient material for planar electrodes and very smooth films of pyrolysed photoresist [5] suitable for applications in molecular electronics [6,7,8]. Another advantage of graphitic carbon is that the surface can be easily modified by methods which give very stable molecular coatings, attached by strong C-C [9] or C-N covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison has been made of transport through junctions containing single molecules with transport through those based on molecular adlayer films; once again, the results highlight the crucial role that contacts play in molecular junction transport. In particular, a substantial reduction in contact resistance has been demonstrated using covalent interactions at carbon electrodes; 17 less effective mixing occurs through Lewis interactions at metal/thiol or isocyano links.…”
Section: Molecular Transport Junctions: An Introductionmentioning
confidence: 99%